Evaluation of Specific Symptoms of Bacterial Vaginosis Among Pregnant Women - J. Boris; T. B. Henriksen; U. Davidsen; N. J. Secher (Hindawi Limited, 1997)
Objective: Identification of the symptoms of bacterial vaginosis (BV) in pregnancy might be rational in order to identify a possible BV-associated group at risk of preterm delivery.